1973
DOI: 10.1139/o73-137
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Absorption and Deposition in Rainbow Trout (Salmo gairdnerii)

Abstract: Rainbow trout, fed or starved for 5 weeks, were force-fed 23 μCi 1-14C-palmitic acid and sacrificed at [Formula: see text], 1, 2, 4, 8, and 14 h after feeding. Analysis of the blood suggested that trout possess an intestinal absorption mechanism for lipid that is very different from that found in other animals. The fish, incapable of delivering triglyceride to its circulation in the usual way, receives most of its absorbed lipid as free fatty acids, probably via the portal system. It was also found that light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 6 publications
3
41
0
1
Order By: Relevance
“…particles into the blood (Robinson and Mead, 1973;Sheridan, 1988). Our medaka NASH model was created by feeding a HFD based on LCFAs, and we believe that many of the consumed LCFAs arrive in the liver as FFA-albumin complexes.…”
Section: Disease Models and Mechanisms 435mentioning
confidence: 99%
“…particles into the blood (Robinson and Mead, 1973;Sheridan, 1988). Our medaka NASH model was created by feeding a HFD based on LCFAs, and we believe that many of the consumed LCFAs arrive in the liver as FFA-albumin complexes.…”
Section: Disease Models and Mechanisms 435mentioning
confidence: 99%
“…The SVS is not associated with the celiac, mesenteric or renal arteries, and no association has been made between increased SVS flow and food intake (P. V. Skov and J.F.S., unpublished observations) (Skov and Bennett, 2004). The SVS, unlike the lymphatic system of mammals (Robinson and Mead, 1973;Kayama and Iijima, 1976), is not involved in uptake from the gut. Therefore, it is clear that the SVS is not functioning in the same way as the mammalian lymphatic system.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…Robinson & Mead (1973) showed that in contrast to the mammals primarily used by DeNiro & Epstein (1977, 1978, fish use the liver and skeletal muscle as the main sites of lipid storage. In general, the liver serves as the storage depot for lipid in bottomdwelling fish (Robinson & Mead 1973), whereas skeletal muscle serves this function in more active species. Furthermore the red lateral-line muscles are known to store more lipid than does dorsal muscle (Robinson & Mead 1973) although the concentration per unit mass/volume is higher in the liver (Table 1).…”
Section: Andmentioning
confidence: 99%